Development of Digital Competence of Future Primary School Teachers: Challenges and Strategies (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
In the digital era, the development of digital competence among future primary school teachers is crucial to prepare them for effectively integrating technology into their teaching practices. This scientific article explores the challenges associated with developing digital competence among future primary school teachers and presents strategies to address these challenges. It highlights the importance of digital competence in enhancing teaching and learning experiences, fostering students' digital literacy, and promoting 21st-century skills. By acknowledging and addressing the challenges and implementing effective strategies, teacher education programs can better equip future primary school teachers with the necessary digital skills to thrive in the modern educational landscape.